On the Importance of the Arrival of New Information - Chumacero, Rómulo (Estudios de Economía, 2016)
This paper develops a framework for evaluating the importance of the arrival of new information for forecasting, estimation, and decision making. By fusing known and recently developed statistical tests and concepts, the paper provides guidelines for detecting outliers, influential observations, innovations, and possible breaks in the end of the sample. The methodology is applied to analyze the Chilean CPI inflation.